2008
DOI: 10.1111/j.1528-1167.2008.01448.x
|View full text |Cite
|
Sign up to set email alerts
|

The socioeconomic, cultural, and emotional implications of starting or withholding treatment in a patient with a first seizure

Abstract: SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…Diagnosis of epilepsy after a single seizure may engender over‐treatment. The decision to treat or not after a single seizure is complex (Heaney et al., 2008). However, the imperative to offer treatment in the presence of a diagnosis of epilepsy is great.…”
Section: Con: Epilepsy Should Not Be Diagnosed Until a Second Unprovomentioning
confidence: 99%
“…Diagnosis of epilepsy after a single seizure may engender over‐treatment. The decision to treat or not after a single seizure is complex (Heaney et al., 2008). However, the imperative to offer treatment in the presence of a diagnosis of epilepsy is great.…”
Section: Con: Epilepsy Should Not Be Diagnosed Until a Second Unprovomentioning
confidence: 99%
“…(Berg et al, 2010, p. 676) Epilepsy is among the most common serious neurological conditions with incidence rates, in highincome countries, ranging between 40 and 70 per 100 000 persons per year and generally higher in young children and in the elderly (Duncan, 2006;MacDonald, 2000). In resource-poor countries, the incidence is usually much higher, often above 120/100 000/year, and in high-income countries, poor people also seem to have a higher incidence (Heaney 2008;. Prevalence studies have reported lifetime rates between 4 and 10/1000 in developed countries (Forsgren, 2005) but data from poor countries suggest prevalence rates of 23.2-32.1/1000 (Bell, 2014) up to 57/1000 in some rural areas (Sander, 1996).…”
Section: Epilepsymentioning
confidence: 99%
“…When faced with a first unprovoked seizure, the patient/family will consider many factors that influence the decision of whether to pursue antiepileptic treatment. 58 Some families are willing to start antiepileptic treatment based on fear or anxiety about the occurrence of the next seizure, lifestyle limitations, employment concerns, or driving restrictions. 58 Others are not willing to seek antiepileptic treatment because of the associated risks: cognitive side effects, physical side effects (ie, weight gain), stigma, and teratogenicity in women of child-bearing age.…”
Section: Management Approachmentioning
confidence: 99%